Performance Analysis of a 1-Slot 1-Pole Orbital Electric Motor with Rotor Variations Using ANSYS Electronics - Bagus Akbar Prihartanto; Widya Aryadi (Universitas Negeri Semarang, 2026)
Global warming and rising carbon emissions from the transportation sector have accelerated the development of electric vehicles, making the selection of an appropriate electric motor design essential. This study examines the performance characteristics of a ring-type orbital electric motor with a 1-slot 1-pole configuration by comparing two rotor materials, namely pure permanent magnet (Neodymium NdFe30) and low carbon steel (Steel 1010), in terms of flux linkage, electromagnetic force, and torque. Simulations were conducted using ANSYS Maxwell, a Finite Element Method (FEM)-based tool within ANSYS Electronics, employing a Magnetostatic Solver across a rotor rotation angle range of -50° to 50° with a 1° step. The results show that the low carbon steel rotor produced a higher maximum force and torque than the pure permanent magnet rotor, reaching 362.373 N (217% higher than 114.427 N) and 146.829 Nm (17.5% higher than 124.944 Nm), respectively. For flux linkage, both rotors exhibited similar baseline values but moved in opposite directions as the rotor approached its central position, with the low carbon steel rotor increasing to 1.62377 Wb and the pure permanent magnet rotor decreasing to -0.260653 Wb, resulting in a deviation approximately 64.3% larger for the low carbon steel rotor. Across all three parameters, the low carbon steel rotor exhibited sharper and more concentrated fluctuations, whereas the pure permanent magnet rotor produced smoother, more stable, and evenly distributed responses throughout the tested angular range.